Housing status, mental health, and help-seeking among American Indian and Alaska Native Veterans in the Midwest - Umucu, Emre; Lee, Beatrice; Chang, Chi; Tsai, Jack (Frontiers in Public Health, 2025)
ObjectiveThis study aims to examine mental health and help-seeking behaviors among homeless and unstably housed (HUH) and stably housed (SH) American Indian and Alaska Native (AIAN) and non-AIAN veterans in the Midwest.MethodsThe study cohort consisted of veterans in the Veterans Affairs (VA) service catchment area called the Veterans Integrated Service Network (VISN) 23. Data from the Homeless Operations Management and Evaluation System (HOMES) were analyzed with descriptive statistics and the Mantel–Haenszel odds ratio with Wald confidence intervals, and the Breslow-Day test.ResultsOf the 7,260 veterans in the study, 5,771 (80/9%) were HUH. Among non-AIAN participants, 5,453 (80.8%) experienced HUH, compared to 318 (84.6%) of AIAN veterans. The Breslow-Day test revealed significant differences in the association between housing status and certain service needs between AIAN and non-AIAN veterans.ConclusionThis study highlights notable differences in housing status, mental health conditions, and service needs between AIAN and non-AIAN veterans in the Midwest.